POLYMER - BITUMEN COMPOSITES PROPERTIES OF THE INGREDIENTS USED FOR OBTAINING (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Multifunctional ingredients have been created to obtain polymer-bitumen compositions used in changing weather conditions by crushing used rubber-technical products and tires on the basis of mechanical forces . The effect of the created modifiers and ingredients on the heat, cold, friction, elongation, compression resistance and rheological, technological, physical-mechanical, dynamic properties of the polymer-bitumen composition was determined.